Dental Care in an Equal Access System Valuing Equity: Are There Racial Disparities?. Issue 11 (November 2016) - Boehmer, Ulrike; Glickman, Mark; Jones, Judith A.; Orner, Michelle B.; Wheler, Carolyn; Berlowitz, Dan R.; Kressin, Nancy R.
Abstract : Background: Racial disparities in dental care have previously been shown in the Veterans Health Administration (VA)—a controlled access setting valuing equitable, high-quality care. Objectives: The aim of this study is to examine current disparities in dental care by focusing on the receipt of root canal therapy (RCT) versus tooth extraction. Research Design: This is a retrospective analysis of data contained in the VA's electronic health records. We performed logistic regressions on the independent measures along with a facility-specific random effect, using dependent binary variables that distinguished RCT from tooth extraction procedures. Subjects: VA outpatients who had at least 1 tooth extraction or RCT visit in the VA in fiscal year 2011. Measures: A dependent binary measure of tooth extraction or RCT. Other measures are medical record data on medical comorbidities, dental morbidity, prior dental utilization, and demographic characteristics. Results: The overall rate of preferred tooth-preserving RCT was 18.1% during the study period. Black and Asian patients were most dissimilar with respect to dental morbidity, medical and psychological disorders, and black patients had the least amount of eligibility for comprehensive dental care. After adjustment for known confounding factors of RCT, black patients had the lowest RCT rates, whereas Asians had the highest. Conclusions: Current quality improvement efforts and a value to improve the equity of care are not sufficient to address racial/ethnic disparities in VA dental care; rather more targeted efforts will be needed to achieve equity for all.